A spatial simulation model to assess controls upon grassland degradation on the Qinghai-Tibet Plateau, China. (September 2018) - Li, Xilai; Perry, George L.W.; Brierley, Gary J.
Abstract: Large areas of alpine meadow across the Qinghai-Tibet Plateau (QTP), western China, are undergoing degradation. Drawing upon field and remotely sensed data we develop a spatially explicit grid-based simulation model to explore the long-term dynamics of alpine meadow communities in this area. Our model represents the spatial dynamics of four plant functional types (PFTs) – sedges, grasses, forbs and weeds – together with disturbance from livestock grazing and small mammal activity. The model is most sensitive to parameters related to the reproductive rate and lifespan of the three plant functional types. Comparisons between model outcomes and field observations of vegetation composition suggest that the model produces plausible predictions of community dynamics. Simulation experiments indicate that grazing intensity is a fundamental control of plant community dynamics in these ecosystems. As grazing intensity increases there is a shift from a community dominated by grasses and forbs (very low grazing level) to grasses and sedges (low and moderate grazing levels) to degraded ground (high grazing levels). Severely degraded alpine meadows (locally termed 'Heitutan' or 'black beach') emerge after 370 simulation years under high levels of grazing pressure, but after only two decades under extreme grazing pressure. Under low to moderate intensity grazing regimes small mammals play an important role in maintaining meadow ecosystems. However, our model suggests that small mammal activity is no longer beneficial to the grassland ecosystem under high grazing pressures, increasing the rate of Heitutan formation. The time frame for a return to a sedge-dominated community is shortest under a moderate intensity grazing regime, but even in this instance it may take several hundred years. Highlights: We developed a spatially explicit imulation model of alpine meadow dynamics on the Qinghai-Tibet Plateau. The model suggests that grazing regime is a key factor in patterns of meadow degradation. Restoring degraded areas of alpine meadow may be an extremely slow process.